Comparative Assessment of Knowledge, Attitudes, and Practice of Breast Self-Examination among Female Secondary and Tertiary School Students in Ghana - Linda Ahenkorah Fondjo; Osei Owusu-Afriyie; Samuel Asamoah Sakyi; Akua Addo Wiafe; Bright Amankwaa; Emmanuel Acheampong; Richard K. D. Ephraim; William K. B. A. Owiredu (International Journal of Breast Cancer)
Background. Breast cancer remains a serious public health problem globally. It is particularly increasing among adolescents and premenopausal women. Breast self-examination (BSE) is the most effective and feasible means of detecting breast cancer early in developing countries. This study aimed at evaluating and comparing knowledge of BSE among secondary and tertiary school students and at revealing their attitudes and practices about BSE. Method. This cross-sectional study was conducted among 1036 female secondary and tertiary school students of Kwame Nkrumah University of Science and Technology and Technology Senior High School. Data was obtained using a pretested questionnaire to access sociodemography, knowledge, attitudes, and practice of BSE among the students. Result. Most students were within the age of 15–24 years; 90.9% were aware of BSE. A high level of knowledge on BSE was found in 54.5% of the students. Knowledge was significantly higher in tertiary than secondary school students (p=0.002). 24.1% of the students thought BSE could be performed anytime; however only 8.1% of the students performed BSE monthly as recommended, whilst 41.8% had never practiced. Of these, more secondary students had never practiced BSE as compared to the tertiary students. 22.3% indicated they would wait for a change in a detected breast lump before seeking medical attention. 96.3% of the participants agree BSE is a good practice which must be encouraged. Conclusion. Teaching of BSE should be intensified beginning at the high school level, emphasizing practice and its benefits for early detection of breast cancer.